Effect of certain indigenous technical knowledge on the management of red spider mite (Oligonychus coffeae) in tea - Gautam Kumar Saikia, Kapil Kumar Bhuyan; Subhash Chandra Barua, Mukul Kumar Deka (Journal of Plantation Crops, 2017)
An investigation was carried out at Deha Tea Estate, Jorhat, Assam during 2015-16 by using different indigenous technical knowledge (ITK) prevalent among different small tea growers. Fish extract at (0.25, 0.5 and 1%), Polygonum hydropiper at (2.5, 5 and 7.5%) and Azadirachtin (Neemazal-F 5%) were evaluated in field conditions against tea mite. The result showed that fish extract in combination with cow dung, cow urine and water when sprayed at one per cent concentration, significantly reduced red spider mite population (96.5%), percentage of leaves infestation (5.2%) and leaf area infested by the mite (11.6%). P. hydropiper in combination with cow urine and water when sprayed at 7.5 per cent concentration significantly reduced red spider mite population (87.5%), percentage of infestation (9.1%) and leaf area infested by the mite (12.9%). Among all the ITKs, fish extract at one per cent caused higher reduction of infestation of red spider mite followed by P. hydropiper extract at 7.5 per cent. Influence of both the treatments on the management of red spider mite was at par with that of commercial Azadirachtin.